2020
DOI: 10.5194/acp-2020-1009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal analysis of submicron aerosol in Old Delhi using high resolution aerosol mass spectrometry: Chemical characterisation, source apportionment and new marker identification

Abstract: Abstract. We present the first real-time composition of submicron particulate matter (PM1) in Old Delhi using high resolution aerosol mass spectrometry (HR-AMS). Old Delhi is one of the most polluted locations in the world, and PM1 concentrations reached ~ 600 µg m−3 during the most polluted period, the post-monsoon, where PM1 increased by 178 % over the pre-monsoon period. Using positive matrix factorisation (PMF) to perform source apportionment analysis, two burning-related factors contribute the most (35 %)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…This shows both the importance of primary sources and the fact that daily average temperatures remain above 20 • C throughout the year; 20 • C in winter and 43 • C pre-monsoon, compared, for example, with European urban environments where average temperatures can drop to 5 • C or lower in winter and summer temperatures are around 25-30 • C. This temperature might increase the regional pollutant transport allowing an even POA-SOA distribution over the Delhi region. When comparing these results with Cash et al (2021), it shows the importance POA has in OD during the post-monsoon season, where a POA relative contribution of 63 % is observed. Meteorology played an important role in aerosol concentrations.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This shows both the importance of primary sources and the fact that daily average temperatures remain above 20 • C throughout the year; 20 • C in winter and 43 • C pre-monsoon, compared, for example, with European urban environments where average temperatures can drop to 5 • C or lower in winter and summer temperatures are around 25-30 • C. This temperature might increase the regional pollutant transport allowing an even POA-SOA distribution over the Delhi region. When comparing these results with Cash et al (2021), it shows the importance POA has in OD during the post-monsoon season, where a POA relative contribution of 63 % is observed. Meteorology played an important role in aerosol concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…These POA relative contributions close to 50 % over different times of the year have been previously observed in a study performed in 2017 at IIT Delhi, New Delhi (Bhandari et al, 2020), with similar average concentrations for POAs and OOAs (52 and 56 µg m −3 , respectively, for winter as well as 30 and 31 mug m −3 , respectively, for pre-monsoon). Cash et al (2021) identified POA relative contributions of 45 % and 52 % for pre-monsoon and monsoon and 64 % for post-monsoon, showing the importance of POA concentrations in OD during this latter season. OOA concentrations are produced by both POAs and precursor gas.…”
Section: Organic Aerosol Sources and Their Contribution To Nr-pmmentioning
confidence: 89%
See 3 more Smart Citations